Reconstruction and current status of the Helimak device in China - ZHU, Xiang; LIN, Xiaodong; WU, Muquan; LI, Hang; LI, Jingchun; HAO, Baolong; LIU, Ying; GAO, Xiang; LI, Jiangang; GENTLE, Kenneth W. (Plasma science & technology, 2025)
The Texas Helimak device, operated by the University of Texas at Austin, USA, has been reconstructed at Shenzhen University in China. The device was shipped to Shenzhen University at the end of 2019. Over the following three years, various support systems, including the magnet (toroidal field and vertical field) power supply system, vacuum system, electron cyclotron resonance heating (ECRH) system, fueling system, central control system, and so on, underwent comprehensive replacements and upgrades, with only the original vacuum chamber and magnets retained. By the end of 2022, the reconstructed Helimak device successfully produced stable helium plasmas for the first time in China. Over the next two years, several diagnostic systems were progressively installed and put into operation. Based on the characteristics of the Helimak device, research work will include studies and simulations of plasma behavior in the scrape-off layer (SOL) region of tokamak devices, investigations of plasma–wall interactions (PWIs), and research into the efficiency of ECRH plasma cleaning of the first wall. At the same time, we will continue to upgrade and modify the Helimak device as needed, aiming to establish it as a high-quality experimental platform for magnetic confinement fusion research. The device is now operating regularly for experimental purposes at Shenzhen University.